The impact of using visual programming environments on the development of computational thinking and transdisciplinary competencies in middle school education - Tatiana VEVERITA (Acta et Commentationes, Sciences of Education, 2025)
The article investigates the impact of using visual programming environments, particularly the Scratch platform, on the development of computational thinking and transdisciplinary competencies among 9th-grade students in secondary education. The study is based on the analysis of integrating a modular textbook, developed according to the national curriculum, which combines practical activities, creative projects, and modern pedagogical strategies, including project-based learning and an interactive approach.Assessments applied to an experimental group and a control group, conducted in three stages over a semester, highlight a significant increase in cognitive performance, motivation, and quality of results in the experimental group. The data indicate that the use of Scratch supports the development of solid algorithmic thinking and facilitates the transfer of knowledge to interdisciplinary contexts, thereby contributing to the formation of complex digital and transdisciplinary competencies.The conclusions emphasize the value of visual programming environments as an effective teaching tool in contemporary digital education and recommend their systematic integration across various disciplines to support pedagogical innovation and essential 21st-century skills for students.